Physico‐chemical changes in guava (Psidium guajava L.) during development and maturation - Yusof, Salmah; Mohamed, Suhaila (John Wiley & Sons, 1987)
Guava of the Vietnamese variety is commercially grown in Malaysia. To obtain a better understanding of the fruit, the physical and chemical changes occurring during development and maturation were studied. The weight increase, reduction in hardness, total pectin content, and changes in glucose and ascorbic acid levels showed a sigmoid curve. The maximum weight and glucose increases occurred between weeks 10 and 12. Reduction in hardness, and changes in pectin and ascorbic acid content occurred most between weeks 12 and 14. Reduction in chlorophyll content, and increase in fruit diameter, fructose content and water soluble pectin fraction showed a more linear change. Fructose level was highest among the three sugars (fructose, glucose and sucrose) monitored during maturity. The density of the fruit increased rapidly at the beginning, remained constant between weeks 4 and 12 and then decreased again. The moisture content increased rapidly at first, followed by a more gradual increase and remained constant after week 14. The pH and percentage titratable acidity of the Vietnamese guava fluctuated, being fairly acidic at week 4 (pH 4.5), least acidic at week 10 (pH 5.4) and acidic again on maturity (pH 4.05). The tannin level was high in immature guava but dropped drastically after week 8, and remained at a constant low level after week 10. Soluble pectin increased during development and maturity. Insoluble pectin (NaOH soluble) increased during development but was converted to soluble pectin during maturity (after week 14).